Cutaneous Vasculitis and Central Nervous System Infarctions due to Varicella Zoster Virus Vasculopathy in an Immunocompromised Patient - Karen Flores Rosario; Katherine C. Michelis; Carol Bjorkman; Faris G. Araj (Case Reports in Transplantation)
Varicella zoster virus (VZV) infection commonly presents as varicella during childhood, and zoster, later in life. Here, we present a rare and interesting case of VZV infection that manifested with both cerebral and spinal infarctions and cutaneous vasculitis in the absence of a classic vesicular rash in an immunocompromised patient.